?TRACE METAL BUILD UP IN THE MARINE ENVIRONMENT OF SOUTH WEST COAST OF PAKISTAN: EVIDENCE FROM THE EDIBLE FISH MUSCLE (Biological Sciences - PJSIR, 2000)
Six species of commercially important fish (Arttis thalassinus, Gymnura poecilura, Lutjanus fulviflamma, Nimipterius japonicus, Platycephalus indicus and Seriolina nigrofasciata) captured from the northern coast 'of the Arabian Sea, Pakistan were analyzed for eleven trace metals (Ag, As,Cd, Cr,Cu, Fe, Mn, Ni,Pb, Zn and Hg)and four macronutrients (Na, K, Ca and Mg) using graphite furnace atomic absorption spectrometer to assess the current extent of metal pollu- tion in the coastal waters. In order to evaluate trace metal enrichment in the fish over a time period, a set of elemental data obtained during 1987for a commercial fish, Aruis thalasslnus, was compared with the present data. This compari- son revealed that almost all trace metals in the presently investigated fish exhibited enrichment compared with 1987 metal levels. The percent enrichment (% E year') was found to be maximum for Cr (15.5% year'), followed by Pb (13.24% year'). Zinc showed minimum % E year:' at 5.51 %. The study revealed that Lutjanus fulviflamma was a good bioaccumulator for As, Cr, Cu, Fe and Zn, and Platycephalus indicus for Cd, Mn, Ni, Pb and Mg.